Determination of Electrical Power for Lighting Distribution Using LED Lights on KM. Tuna Kita - Suardi, Suardi; Sitorus, Chris Jeremy Verian; Kustiwansa, Harlian; Arifuddin, Andi Mursid Nugraha; Pawara, Muhammad Uswah; Hariyono, Hariyono; Alamsyah, Alamsyah; Cahyani, Alviana Eka; Mubarak, Azhar Aras; Lumenteri, Fido Fortunatus (Naval Architecture Department, Kalimantan Institut of Technology, 2025)
Fishing vessels are specialized ships designed to support commercial fishing operations by integrating various structural and functional elements such as hull dimensions, deck layout, load capacity, crew accommodations, propulsion systems, and supporting equipment. One critical yet often overlooked component of such vessels is the lighting system, which plays a key role not only in ensuring operational safety and visibility but also in enhancing fishing effectiveness, particularly during night operations. Currently, many fishing vessels still rely on conventional fluorescent lighting, which is less energy-efficient and has a shorter operational life compared to modern alternatives such as LED technology. This study addresses the inadequacy of current lighting installations on fishing vessels by proposing a redesigned electrical installation system utilizing LED lamps. The objective is to develop an efficient and functionally optimized lighting plan that reduces energy consumption and operational costs while improving onboard visibility. Additionally, LED lights can serve dual purposes on fishing vessels—not only for general illumination but also as fish-attracting lights, which may contribute to increased catch yields. The research employs the Zonal Cavity Method (also known as the Lumen Method) as the primary analytical approach. This method enables the calculation of illumination levels by considering inter-surface reflectance and dividing each interior space into three distinct zones: the High Ceiling Cavity (HCC), High Room Cavity (HRC), and High Floor Cavity (HFC). Illumination levels are then determined according to established lighting standards for each functional area within the vessel. The results of the analysis demonstrate that LED-based lighting systems significantly outperform fluorescent systems in terms of energy efficiency, uniformity of light distribution, and alignment with lighting standards. Furthermore, the proposed installation plan offers long-term operational benefits, including reduced maintenance requirements and lower power consumption. The findings support the broader adoption of LED lighting in small-scale fishing vessels and suggest further research into integrating solar-based energy systems to enhance sustainability and self-sufficiency in future vessel designs.